(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The most widespread method that directed to reduce credit risk is evaluation of creditworthiness of the organization. Therefore it is relevant to investigate thoroughly the method and procedure of analysis of creditworthiness. The complexness of evaluating creditworthiness leads to apply different methods. The world experiences shows it. There are variety of experience of different countries in evaluating liquidity and creditworthiness, and consequently the applied indicators are differ from each other. This paper considers method and procedure of evaluating creditworthiness based on example JSC ‘Freedom Finance’. Thus, the research shows the role and meaning of the analysis of creditworthiness as a main criteria in developing effective credit relation between bank and client.